Halal Certification Online to Drave Halal Value Chain (HVC) During the Covid-19 Pandemic - Abdul Latif; Moh Agus Nugroho; Andi Mardiana; Aprianti Napu (International Journal of Islamic and Social Sciences (ISOS), 2021)
Halal Value Chains (HVC) have grown quite rapidly over the last five years. This is shown from the number of Indonesian halal food exports to global food exports ranging from 15 to 18% from 2015 to 2020. Thus, the halal label plays an important role in encouraging the increase in the value and transactions of HVC. (Lembaga Pengkajian Pangan Obat-obatan dan Kosmetika) LPPOM MUI, currently has provided (Online Halal Certification Service System) CEROL-SS23000, to speed up and make it easierfor producers to register their products so they can get halal certificates. This study uses a qualitative descriptive approach. The purpose of this study was to find out how the halal certification process carried out by LPPOM-MUI and the development of HVC survived the Covid-19 pandemic. Based on the results of the researcher's analysis, during the LPPOM MUI pandemic, three breakthroughs were made to simplify the halal certification process. First, making adjustments to the audit method known as Modified On Site Audit (MosA), secondly accelerating the halal certification audit process and thirdly extending the validity period of the halal certificate. Although the demand for halal certification has increased, HVC throughout 2020 decreased by a total of -1.72% but this is better than the national GDP level. The PRM (Muslim Friendly Tourism) sector and Muslim fashion were the worst sectors to experience contraction with a percentage decline of -12.53% and -9.87%, respectively. Meanwhile, halal food grew 1.58% and the halal agriculture sector grew 1.85%.